Hydrogenation of CO2 to synthetic natural gas over supported nickel catalyst: effect of support on methane selectivity - Hodala, Janardhan L.; Jung, Jae-Sun; Yang, Eun-Hyeok; Hong, Gi Hoon; Noh, Young Su; Moon, Dong Ju (SPRINGER, 2017)
Nickel-based catalysts were prepared by co-precipitation method and applied for the CO2 conversion to synthetic natural gas. Two batches of catalysts were prepared with the different amount of Ni and were characterized by various techniques such as XRD, TPD, TPR, XPS, and TEM. Catalytic activity was studied under atmospheric pressure, a temperature of 350 A degrees C, GHSV of 2000 h(-1) and N-2:CO2:H-2 = 4:1:4. Highest CO2 conversion achieved was 70 with 99 % selectivity to methane. The activity of catalysts depends on the nickel content and nickel dispersion. Selectivity to methane depends inversely on the concentration of weak and moderate strength basic sites. Comparable quantity of basic sites present over catalysts, the methane selectivity is observed to be similar but the CO2 conversion changed due to change in Ni content. Catalysts having equal amounts of Ni exhibited increase in CH4 selectivity with the decrease in basic sites.
Keywords: CARBON-DIOXIDE; LOW-TEMPERATURE; KINETICS; RH/TIO2; SYNGAS; FE